Postoperative use of the chemopreventive vitamin K2 analog in patients with hepatocellular carcinoma. - Jian-Hong Zhong (Public Library of Science (PLoS), 2013)
Aim To evaluate the chemopreventive efficacy of vitamin K2 (VK2) analog in patients with hepatocellular carcinoma (HCC) after curative hepatic resection or local ablation, since a recent randomized control trial (RCT) and systematic review have given contradictory results. Methods MEDLINE, EMBASE and Cochrane library databases were systematically searched through the end of May 2012. Meta-analysis of RCTs and cohort studies was performed to estimate the effects of the VK2 analog on tumor recurrence rate and overall survival (OS). Risk ratios (RRs) and 95% confidence intervals (95% CIs) were calculated. Results Six RCTs and one cohort study involving a total of 930 patients were included. VK2 analog therapy did not reduce the 1-year recurrence rate, with a pooled RR of 0.67 (95% CI 0.39-1.13, p = 0.13). However, VK2 analog therapy was associated with a significant reduction in the 2- and 3-year tumor recurrence rates, with respective pooled RRs of 0.65 (95% CI 0.51-0.83, p<0.001) and 0.70 (95% CI = 0.58-0.85, p<0.001). The therapy was also associated with a significant improvement in 1-, 2-, and 3-year OS, with respective pooled RRs of 1.03 (95% CI 1.01-1.05, p = 0.02), 1.11 (95% CI 1.03-1.19, p = 0.005) and 1.14 (95% CI 1.02-1.28, p = 0.02). None of the studies reported adverse effects attributable to VK2 analog therapy. Conclusion The VK2 analog may reduce recurrence rate after 1 year and improve OS in HCC patients as early as 1 year. However, these findings should be considered preliminary since the majority of patients came from an RCT with survival data out to only 1 year. More extensive studies with larger sample sizes and longer follow-up are needed.